Carotid circulation in amniotes and its implications for turtle relationships - Müller, Johannes (2011)
The pattern of carotid blood vessel circulation in the skull of amniote vertebrates is reviewed, considering both fossil and extant taxa. Based on comparisons of early synapsids, mammaliaforms, eureptiles, parareptiles, as well as amniote outgroups, it is shown that in most amniotes the cerebral branch of the carotid artery separates from the palatal branch prior to entering the braincase, with the cerebral branch piercing the basisphenoid ventrally and exiting within the pituitary fossa, and the palatal branch continuing in an anterior direction ventral to the braincase. In squamates and parareptiles this pattern is different in that the carotid artery enters the braincase dorsolaterally to the basipterygoid process, and the palatine and the cerebral branches separate from each other inside the bone and exit within the pituitary fossa. Birds, crown turtles, and some sauropterygians display a pattern which at least to some extent resembles that of squamates and parareptiles. Optimization of patterns of carotid circulation on a generalized amniote phylogeny with variable placement of turtles indicates that independent of turtle position, the separation of cerebral and palatal branch prior to entering the braincase must be considered plesiomorphic for amniotes. Because early turtles such as Proganochelys also retain the plesiomorphic condition, carotid circulation does not support a grouping of turtles within parareptiles.